Preliminary assessment of the impact of climate change on design rainfall IFD curves - Bates, B.; Argueso, D.; Evans, J.; Green, J.; Griesser, A.; Jakob, D.; Seed, A.; Lau, R.; Lehmann, E.; Phatak, Aloke; Abbs, D.; Lavender, S.; et al. (2015)
The new edition of Australian Rainfall and Runoff (hereafter designated ARR 2015) contains completely revised design rainfall Intensity-Frequency-Duration (IFD) curves prepared by the Bureau of Meteorology. These curves are estimated from current climate observations. The Fifth Assessment Report of the Intergovernmental Panel on Climate Change states that "extreme precipitation events over most of the mid-latitude land masses and over wet tropical regions will very likely become more intense and more frequent by the end of this century, as global mean surface temperature increases." This suggests that the current-climate IFD curves may become unsuitable for infrastructure design in future decades. While ARR 2015 includes an interim guideline on incorporating climate change into design flood estimation, the guidance is based on a 'broad brush' approach due to the paucity of published regionally specific results. As a first step towards bridging this gap, a pilot project titled 'Rainfall Intensity-Frequency-Duration (IFD) Relationships under Climate Change' was commissioned in June 2013 and administered by Engineers Australia. Its principal aim was to provide insight into how the new design rainfall IFD curves might be affected by anthropogenic climate change. This paper describes the background for and components of the investigation, the challenges involved, the major research findings and recommendations for further action.